Molecular Interactions of Mefenamic Acid with Lipid Bilayers and Red Blood Cells (2011)
ABSTRACT: Mefenamic acid is a nonsteroidal anti-inflammatory drug (NSAID), also prescribed to treat pain. In the present work, the structural effects on the human erythrocyte membrane and molecular models have been investigated. The latter consisted in bilayers built-up of dimyristoylphosphatidylcholine (DMPC) and dimyristoylphosphatidylethanolamine (DMPE), classes of lipids found in the outer and inner moieties of the erythrocyte and most cell membranes, respectively. This report presents evidence that mefenamic acid interacts with red cell membranes as follows: (i) in scanning electron microscopy (SEM) studies on human erythrocytes it has been observed that the drug induced shape changes, forming stomatocytes; (ii) X-ray diffraction showed that the drug interacted with DMPC bilayers; somewhat lower perturbing effects on DMPE were detected; (iii) FT-IR measurements showed that NSAID induced fluidization of both DMPC and DMPE acyl chains; (iv) Förster resonance energy transfer spectroscopy (FRET) indicated a rapid intercalation of the mefenamic acid into DMPC liposome hydrophobic chains.